Influence of relationship marketing on paddy farm performance in Bangladesh - Iris, Farhana (2021)
Nowadays, many firms/individuals are moving towards business relationships, becoming closer, and developing business ties with their business partners in the supply chain. Relationship marketing could underpin strategic marketing to minimize economic problems and enhance performance. It is considered a way of reducing cost, enhancing efficiency, increasing profit and competitive advantage, and improving personal relationships. Nonetheless, the business transaction between paddy buyers and farmers are not efficient in terms of economic return for farmers in Bangladesh. The commencement of modernization draws much theoretical debate and practical concern, some of which have received little research attention, especially the influence of relationship marketing on the farm performance of the farmers. The strategic use of relationship marketing is essential for both farmers and marketers. This study developed a model of relationship marketing based on existing literature to empirically investigate the influence of relationship marketing on the farm performance of paddy farmers in Bangladesh. Specifically, this study aimed to examine the direct and indirect influences of relationship marketing on farm performance and considered the mediation effects of satisfaction and loyalty. The dimensions of relationship marketing, namely trust, commitment, communication, and power, were employed in the study as independent variables, satisfaction and loyalty as mediating variables and farm performance as the dependent variable. Primary data was collected through a quantitative survey-based approach with 356 farmers interviewed from the Mymensingh district of Bangladesh. The survey used a structured questionnaire with a 7-point Likert scale. A systematic random sampling technique was used to collect data. Descriptive analysis was employed to summarize the farmers’ demographic profiles, farmers’ attitudes, and experiences towards their preferred buyers. Partial Least Square Structure Equation Modelling (PLS-SEM) was employed to test the hypotheses developed in this study. The findings revealed that trust, communication, satisfaction, and loyalty were positively related to farm performance. Trust, commitment, communication, and power had indirect relationships with performance in the presence of satisfaction and loyalty. It indicates that satisfaction and loyalty were the key mediators between relationship marketing and the farmers’ business relationship. The results also showed that trust, commitment, communication, and power had significant relationships with satisfaction and loyalty. These findings are a valuable insight into the relationship marketing and farmers’ farm performance, especially in terms of profit, sales, and cash flow growth. It also set a step forward to developing a unified theoretical framework for understanding the role of relationship marketing and the mediating roles of satisfaction and loyalty on farmers’ farm performance. The findings will also serve the policymakers as a basis for formulating essential policies and procedures introducing relationship marketing as a marketing strategy. In turn, it will help inspire paddy farmers and buyers to practice relationship marketing to ensure improved farm performance, especially for Bangladeshi farmers.